2020
DOI: 10.4269/ajtmh.20-1015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Country-wide Coronavirus Mortality with Demographics, Testing, Lockdowns, and Public Wearing of Masks

Abstract: We studied sources of variation between countries in per-capita mortality from COVID-19 (caused by the SARS-CoV-2 virus). Potential predictors of per-capita coronavirus-related mortality in 200 countries by May 9, 2020 were examined, including age, gender, obesity prevalence, temperature, urbanization, smoking, duration of the outbreak, lockdowns, viral testing, contact-tracing policies, and public mask-wearing norms and policies. Multivariable linear regression analysis was performed. In univariate analysis, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
220
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(239 citation statements)
references
References 62 publications
4
220
1
9
Order By: Relevance
“…Their models estimated that 80-90% masking would eventually eliminate the disease. They also looked at an empirical dataset, similar to those of Leffler et al and Goldman Sachs (31,34), finding a very strong correlation between early universal masking and successful suppression of daily case growth rates and/or reduction from peak daily case growth rates, as predicted by their theoretical simulations.…”
Section: Population Impactmentioning
confidence: 75%
See 2 more Smart Citations
“…Their models estimated that 80-90% masking would eventually eliminate the disease. They also looked at an empirical dataset, similar to those of Leffler et al and Goldman Sachs (31,34), finding a very strong correlation between early universal masking and successful suppression of daily case growth rates and/or reduction from peak daily case growth rates, as predicted by their theoretical simulations.…”
Section: Population Impactmentioning
confidence: 75%
“…There are now over 100 countries that have implemented mask requirements (31), and many regions such as US states that have their own mask mandates. Most of these requirements were instituted after there was a shortage of medical masks, so results in these countries are likely to reflect the reality of what masks the public is able to access in practice during a pandemic.…”
Section: Population Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mask wearing prevalence in the U.S. has been variable across regions of the country, compared to 95% adherence in countries where cultural norms or mandates facilitated the practice. 1 In the U.S., there has not yet been a federal mask mandate, although individual counties and states have successively (but not uniformly) instituted individual mandates.…”
Section: Main Textmentioning
confidence: 99%
“…An observational study comparing 34 regions of Ontario, Canada, which introduced mask mandates on different dates, found that in the weeks after implementation, such mandates were associated with 25% fewer new cases of COVID-19 per week ( 46 ). In a study across 200 countries, in those with cultural norms or government policies supporting public masking, per capita mortality from COVID-19 increased by 16.2% per week, compared with 61.9% per week in the remaining countries ( 47 ).…”
Section: Universal Masking Is Associated With Fewer New Cases and Lowmentioning
confidence: 99%